Expanding the Current Knowledge About the Role of Interleukin-10 to Major Concerning Bacteria - Peñaloza, Hernán F.; Noguera, Loreani P.; Riedel, Claudia A.; Bueno, Susan M. (Frontiers in Microbiology, 2018)
Interleukin-10 (IL-10) is one of the most important anti-inflammatory cytokine produced during bacterial infection. Two related phenomena explain the importance of IL-10 production in this context: first, the wide range of cells able to produce this cytokine and second, the wide effects that it causes on target cells. In a previous report we described opposing roles of IL-10 production during bacterial infection. Overall, during infections caused by intracellular bacteria or by pathogens that modulate the inflammatory response, IL-10 production facilitates bacterial persistence and dissemination within the host. Whereas during infections caused by extracellular or highly inflammatory bacteria, IL-10 production reduces host tissue damage and facilitates host survival. Given that these data were obtained using antibiotic susceptible bacteria, the potential application of these studies to multi-drug resistant (MDR) bacteria needs to be evaluated. MDR bacteria can become by 2050 a major death cause worldwide, not only for its ability to resist antimicrobial therapy but also because the virulence of these strains is different as compared to antibiotic susceptible strains. Therefore, it is important to understand the interaction of MDR-bacteria with the immune system during infection. This review discusses the current data about the role of IL-10 during infections caused by major circulating antibiotic resistant bacteria. We conclude that the production of IL-10 improves host survival during infections caused by extracellular or highly inflammatory bacteria, however, it is detrimental during infections caused by intracellular bacteria or bacterial pathogens that modulate the inflammatory response. Importantly, during MDR-bacterial infections a differential IL-10 production has been described, compared to non-MDR bacteria, which might be due to virulence factors specific of MDR bacteria that modulate production of IL-10. This knowledge is important for the development of new therapies against infections caused by these bacteria, where antibiotics effectiveness is dramatically decreasing. Key words: Interleukin-10, Multi-drug resistance, Bacterial infection, Immune response, Host-pathogen interactions.